A Randomized Controlled Trial Comparing Videoconference vs. Face-to-Face Delivery of Behavior Therapy for Youths With Tourette Syndrome in the Time of COVID-19 - Prato, Adriana; Maugeri, Nicoletta; Chiarotti, Flavia; Morcaldi, Lucia; Vicario, Carmelo M.; Barone, Rita; Rizzo, Renata (Frontiers in Psychiatry, 2022)
- Objective: To evaluate the clinical effectiveness of online remote behaviour therapy, compared with face-to-face therapy in reducing tics and co-occurring disorders associated with the tics in a sample of youths with Tourette Syndrome. - Design: A randomized controlled trial. TS patients were randomized to receive face-to-face or online remote behaviour therapy. - Participants: 40 children aged between 9 and 16 years affected by Tourette Syndrome. - Results: online remote and face-to-face behaviour therapy are equally effective in the treatment of tics and co-occurring disorders in children and adolescents affected by Tourette Syndrome. Both groups showed an improvement in the severity of tics, obsessive-compulsive symptoms, and anxiety symptoms, as assessed by neuropsychological findings. Online remote behaviour therapy was more effective for reducing depressive symptoms than face-to-face behaviour therapy. - Conclusions: Online remote behaviour therapy is a promising tool for behavioural therapies for patients with Tourette Syndrome and may represents an alternative treatment option.